KONTRIBUSI KYAI KAMPUNG DALAM PENGUATAN RELIGIUSITAS REMAJA DI DESA BLUMBUNGAN - Rofik, Moh; Sadili, Imam (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: Teenagers in Blumbungan village show a tendency towards deviant behavior such as illegal racing, promiscuity, and the adoption of a hedonistic lifestyle influenced by Western culture. Through cultural da'wah with intensive involvement of village kyai which is participatory and contextual, village kyai play an active role in building religious awareness of teenagers. This article aims to analyze the contribution of village kyai in strengthening the religiosity of teenagers in Blumbungan Village, Pamekasan, Madura. Method: This study uses an interpretive qualitative method with a case study approach. The determination of informants was carried out using a snowball sampling technique, where the researcher follows recommendations from one informant to another who are considered relevant and understand the research context. There are five informants in this study with details, three kyai and two from local teenagers. The theory of cultural da'wah as an analytical tool in this study which relies on the delivery of Islamic values ​​by paying attention to the social context, customs, and local culture that live in the community. Results: The study shows that the contribution of village kyai is not limited to religious functions, but also serves as a social companion who guides adolescents through direct involvement in religious activities, such as tajhizul mayit (remembrance of the deceased), regular religious studies, and other collective religious activities.